Local economic development for secondary cities of the Sindh Province, Pakistan / Saima Kalwar - Saima , Kalwar (2018)
This research is intended to diagnose the planning strategy gaps in national and local development plans and their impact on local economic development in secondary cities of Sindh province, Pakistan. The research had adopted mixed-methods methodology by using both qualitative and quantitative techniques. The study has covered the agro-based, fisheries, tourism and wholesale retail economic sectors. Key informant interviews, document review, a literature survey and physical observation methods were used for data collection. A total of 90 structured interviews were conducted with agro-based, inland fisheries and tourism officials to obtain their views about the strengths, weaknesses, opportunities and threats (SWOT) of five-year development plans and the Sukkur city master plan developed for the 1988–2015 period. This study has combined the SWOT and economic base analysis techniques of the shift-share, location quotient and economic base multiplier methods. The study also uses the case study approach to investigate the gaps in five-year development plans and master plan strategies, and their root causes and impact on the local economic sectors of Sukkur city (case study) and Sukkur district. The results of the investigation of the five-year development plans reveal the following: the absence of planning strategies for medium and small agro-based industrial, inland fisheries development, and tourism activities in secondary cities; and the high priority of marine fisheries, textile and sugar industries, and tourism activities in the northern areas of Pakistan. The reasons given by experts for these deficiencies are: centralized system of development plans; political uncertainties; power of federal government through the budget release; influence of metropolitan areas on central and provincial governments; misconception of policymakers about tourism development; lack of coordination between federal and provincial organizations; and cross-border threats. The experts strongly claim that the master plans had failed in providing planning strategies for the local economic sectors of Sukkur city and were dominated by physical development. The experts also claimed that due to this planning gap, employment opportunities were only available in construction and the community, social and personal service sectors. Therefore, more than 70% of the employed population of Sukkur city work in these two informal sectors, mostly on daily wages. Sukkur city is a central trading hub for Northern Sindh, is rich in historical heritage, and is geographically advantaged by being situated on the right bank of the River Indus. However, due to the absence of planning strategies for tourism development, conservation of historical places and supporting infrastructure, it has failed to attract more tourists and to boost wholesale retail activities. Key informant suggestions formed the basis for proposing the strategies needed at provincial and local levels. In order to achieve economic regeneration of secondary cities and their respective regions in Sindh province, the necessary action is a re-look at the five-year development plans, be it at provincial or district level, to minimize planning gaps. Furthermore, attention should be directed to strategic physio-socio-economic aspect planning. The decision-making process also needs to be autonomous at provincial and local levels.